High-thermal-plasticity 980MPa-grade ultrahigh-strength automobile steel and manufacturing method thereof
By optimizing the alloy composition and process, rare earth wires are added to the converter steel discharge and crystallizer to modify and refine the inclusions in the steel, the problems of casting cracks and large-sized inclusions in the production process of ultra-high strength automotive steel are solved, and the thermoplasticity and material yield of steel are improved.
Patent Information
- Application Number
- CN202311246512.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-26
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2043-09-26
AI Technical Summary
Ultra-high-strength automotive steel is prone to produce cast-bill cracks and large-sized inclusions during the production process, affecting the material yield and production efficiency.
By optimizing the alloy composition design and manufacturing process, pre-deoxygenation of ferrosilicon in the converter steel discharge process, and rare earth wires are fed into the crystallizer to modify and refine the inclusions in the steel to form Al-Ca-Ce composite inclusions, improving the purity of the steel and the thermoplasticity of the casting billet.
It effectively reduces the generation of casting cracks, refines inclusions, improves the thermoplasticity and material yield of ultra-high strength automotive steel, and reduces the production cost and production efficiency.
Smart Images

Figure CN119710476A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of iron and steel metallurgy and iron and steel material technology, and in particular to a high-heat-plastic 980MPa-grade ultra-high-strength automobile steel and a manufacturing method thereof. Background Art
[0002] With the continuous improvement of people's requirements for automobile safety and the increasing attention to environmental protection, the development of ultra-high-strength automobile steel is also getting faster and faster. Ultra-high-strength automobile steel is generally used in the B-pillars, control arms, floor brackets, connecting rods and various reinforcements and chassis and other structural parts of the car, which plays an important role in the safety of the car. If ultra-high-strength steel is used, the weight of the whole vehicle will be greatly reduced while ensuring that the strength is not reduced. High-strength automobile steel is an effective means to solve the problem of lightweight. Under the condition of ensuring the safety performance of the car, optimizing the design to thin the body parts can not only effectively reduce the weight of the car body and reduce fuel consumption, but also improve the comfort of passengers.
[0003] Although ultra-high-strength automotive steel has high strength, due to its high alloy content, it is easy to produce cracks in the ingot during the production process, which affects the overall yield rate, resulting in increased production costs and reduced production efficiency. At the same time, large-sized inclusions in the steel will also affect the quality of the ingot. Therefore, how to reduce the occurrence of cracks in the ingot and reduce large-sized inclusions are still urgent problems to be solved in the production process of ultra-high-strength automotive steel.
[0004] Chinese patent CN 106609313 B provides a method for processing high-purity rare earth steel, in which rare earths of different contents are added in the three processes of LF refining, VD / RH vacuum treatment and soft blowing, so as to obtain rare earth inclusions of small size; however, this technology requires adding rare earths in the three processes of LF refining, VD / RH vacuum treatment and soft blowing, which is cumbersome to operate and consumes a large amount of rare earths. Moreover, this technology cannot reduce the occurrence of cracks in the ingot, and is not applicable to ultra-high-strength automotive steel.
[0005] Chinese patent CN 110257590 B provides a method for refining inclusions in high-cleanliness rare earth electroslag steel, adding rare earths during the electroslag remelting process, thereby significantly reducing the oxygen content in the steel. This technology is only applicable to electroslag steel, not non-electroslag steel, and this technology cannot reduce the generation of cracks in the ingot.
[0006] There are also some technologies in the prior art that feed rare earth wires during the preparation process. For example, Chinese Patent Publication No. CN102310178A discloses a method for solving the center segregation of the ingot. According to the formation mechanism of the center segregation of the ingot, the technology optimizes the continuous casting speed, the superheat of the molten steel poured in the tundish, and the opening degree of the casting machine. At the same time, a nucleating agent is added to the crystallizer, and the secondary cooling section adopts electromagnetic stirring and light pressure at the end of solidification to improve the center segregation of elements such as C, S, and Mn formed by the molten steel enriched with solute elements being closed and unable to exchange with other liquids during the solidification process of the ingot due to selective crystallization; although the technology mentions the measure of feeding rare earth wires in the crystallizer, the purpose of feeding rare earth wires is to improve the degree of center segregation of the ingot. The ultra-high strength automotive steel of the present invention is not mentioned, and the specific wire feeding process is not involved. The rare earth addition process in the continuous casting tundish disclosed in Chinese Patent Publication No. CN1824430A relates to the rare earth addition process in the production of the continuous casting machine. Although the technology adopts the feeding of rare earth wire in the tundish, its purpose is to ensure the uniformity of the rare earth components in the molten steel of the same furnace and solve the problem of producing rare earth steel by a single-machine multi-stream continuous casting machine. Moreover, the steel type of the technology does not mention the ultra-high-strength automotive steel of the present invention.
[0007] In view of the above situation, it is urgent to develop an ultra-high strength automotive steel and a manufacturing method thereof, which can not only refine and modify the inclusions in the steel, refine the inclusions, reduce the large-sized inclusions in the steel, but also reduce the occurrence of cracks in the ingot. Summary of the invention
[0008] In view of the problems in the prior art that ultra-high-strength automobile steel is prone to ingot cracks due to its high alloy content and that large-sized inclusions in the steel affect the quality of the ingot, the purpose of the present invention is to provide a high-heat-plastic 980MPa grade ultra-high-strength automobile steel and a manufacturing method. By optimizing the alloy composition design and manufacturing process, rare earth wires are fed into the crystallizer to modify the inclusions, promote the miniaturization of inclusions in the steel, improve the thermoplasticity of ultra-high-strength automobile steel, and reduce the risk of ingot defects in ultra-high-strength automobile steel.
[0009] To achieve the above object, the present invention adopts the following technical solution:
[0010] The first aspect of the present invention provides a high heat-molding 980MPa grade ultra-high strength automobile steel, comprising the following components in weight percentage: C: 0.1-0.3%, Si: 0.2-0.7%, Mn: 1-3%, Ti: 0.04-0.07%, Al: 0.02-0.07%, Ca: 0.001-0.005%, Ce: 0.0010-0.0050%, Cr: 0.2-0.4%, P≤0.013%, S≤0.002%, and the remainder Fe and unavoidable impurities.
[0011] Preferably, its composition satisfies: Al / Ce=11-40, Ce / S=0.5-3, wherein Al, Ce, and S are the weight percentage contents of the corresponding elements respectively.
[0012] Preferably, among the unavoidable impurities, O≤0.0020%, by weight percentage.
[0013] Preferably, the inclusion type of the high heat-plastic 980MPa grade ultra-high strength automobile steel is Al-Ca-Ce composite inclusion.
[0014] Preferably, in the high heat-molded 980MPa grade ultra-high strength automobile steel, the density of inclusions larger than 5 microns is ≤0.05 / mm 2 , the density of inclusions larger than 1 micron is ≤25 / mm 2 , the average diameter of inclusions is ≤2 microns.
[0015] Preferably, in the high heat-molding 980MPa grade ultra-high strength automobile steel, the proportion of acicular bainite structure is greater than 30%.
[0016] Preferably, the cross-sectional shrinkage of the high heat-plastic 980MPa grade ultra-high strength automobile steel is ≥40%.
[0017] The second aspect of the present invention provides a method for manufacturing the high heat-molding 980 MPa grade ultra-high strength automobile steel as described in the first aspect of the present invention, comprising the following steps:
[0018] S1, smelting, using KR desulfurized hot metal and low-sulfur scrap steel as raw materials, adopting top and bottom combined blowing process in the converter, and controlling the oxygen content of the tapped steel below 600ppm by pre-deoxidation during the converter tapping process;
[0019] S2, LF refining, adding aluminum slag during the LF heating process, adding alloys to adjust the composition of the molten steel after reaching the target temperature, and blowing argon gas at the bottom for stirring;
[0020] S3, RH refining, vacuum composition adjustment is carried out in the RH furnace, titanium alloy is added first for deoxidation, aluminum alloy is added for deoxidation after an interval of 3 to 5 minutes, and other alloys are added to adjust the steel liquid composition to the target value, and calcium wire is fed into the RH furnace for calcium treatment after breaking the vacuum;
[0021] S4, continuous casting wire feeding, control O≤0.002%, S≤0.002% in the tundish steel liquid, and feed rare earth wire into the continuous casting crystallizer.
[0022] Preferably, in step S1:
[0023] The molten iron ratio in the raw material is ≥88%;
[0024] The converter tapping temperature is above 1670-1680°C, and the tapping oxygen is controlled at 500-600ppm; and / or
[0025] The deoxidizer used in the pre-deoxidation process is ferrosilicon, and the amount of ferrosilicon added is 50-200 kg / heat; and / or
[0026] 900-1100 kg / heat of lime is added during the converter tapping process; and / or
[0027] In step S2:
[0028] The amount of aluminum slag added is 100-200 kg / furnace;
[0029] The target temperature is 1620-1630°C;
[0030] The argon gas flow rate is 160-180 L / min, and the stirring time is 4-6 min; and / or
[0031] In step S3:
[0032] During the vacuum component adjustment process, the vacuum degree is controlled to be ≤133Pa and the pure degassing time is ≥10min;
[0033] The amount of the titanium alloy added is 120-140 kg / heat; the amount of the aluminum alloy added is 800-900 kg / heat; and / or
[0034] In step S4:
[0035] During the continuous casting wire feeding process, the wire feeding position is the intersection of 1 / 2 of the distance between the water outlet and the narrow side and 1 / 2 of the narrow surface, and single wire feeding is adopted;
[0036] During the continuous casting wire feeding process, the wire feeding speed is 4-5 m / min;
[0037] The rare earth wire is made of La-Ce alloy with a rare earth content of more than 99% or a rare earth wire with an external iron shell with a Ce content of 55-65%.
[0038] Preferably, in the La-Ce alloy having a rare earth content of more than 99%, the content of La is 25-35wt%, and the content of Ce is 65-85wt%.
[0039] Preferably, when the rare earth wire is La-Ce alloy with a rare earth content of more than 99%, the wire feeding speed is 4-5 m / min, and the steel throughput is ≥3 t / min; or
[0040] When the rare earth wire is a rare earth wire with an outer iron shell Ce content of 55-65%, the wire feeding speed is 6-8m / min, and the steel throughput is ≥3t / min.
[0041] Compared with the existing production technology, the present invention has the following beneficial effects:
[0042] 1. The present invention optimizes the alloy composition design, adds an appropriate amount of Ce element, adds ferrosilicon for pre-deoxidation during the converter steelmaking process, and during the refining process, controls the free oxygen in the steel appropriately, optimizes the deoxidation alloy and the order of adding the alloy, so that Al-Ca-Ce composite inclusions are formed in the molten steel, thereby improving the purity of the molten steel (making O in the steel ≤ 0.0020%).
[0043] 2. The present invention feeds rare earth wires into the crystallizer to refine and modify inclusions. During the wire feeding process, no mold slag deterioration occurs, and no slab inclusion defects occur. During this process, the type of typical inclusions in the ingot is transformed from calcium aluminate to Al-Ca-Ce composite inclusions. Such inclusions promote nucleation and refine grains during the solidification of the ingot.
[0044] 3. The ingot structure of the high heat-molding 980MPa grade ultra-high strength automobile steel of the present invention has fine original austenite grains, uniform distribution of black pearlite structure, a high proportion of acicular bainite (greater than 30%), and improved thermoplasticity of the ingot;
[0045] 4. The present invention utilizes the process of feeding rare earth wire into a crystallizer to refine and modify inclusions in steel, thereby stably producing high-heat-molding 980MPa-grade ultra-high-strength automotive steel. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:
[0047] Figure 1 Schematic diagram of the morphology of typical inclusions in the high heat plastic 980MPa grade ultra-high strength automobile steel of Example 1 of the present invention; (a) is an electron microscope scanning image of the inclusion; (b) is a distribution diagram of the O element in the inclusion, (c) is a distribution diagram of the Al element in the inclusion, (d) is a distribution diagram of the S element in the inclusion, (e) is a distribution diagram of the Ca element in the inclusion, (f) is a distribution diagram of the Ce element in the inclusion, (g) is a distribution diagram of the La element in the inclusion, and (h) is a distribution diagram of the Fe element in the inclusion;
[0048] Figure 2Schematic diagram of the morphology of typical inclusions in the steel of Comparative Example 1; (a) is an electron microscope scanning image of the inclusion; (b) is a distribution diagram of the O element in the inclusion, (c) is a distribution diagram of the Ca element in the inclusion, (d) is a distribution diagram of the Al element in the inclusion, (e) is a distribution diagram of the S element in the inclusion, and (f) is a distribution diagram of the Fe element in the inclusion;
[0049] Figure 3 The metallographic images of the ingot structure in the embodiments of the present invention are as follows; (a) is the metallographic image of the ingot structure in Embodiment 1; (b) is the metallographic image of the ingot structure in Embodiment 2; (c) is the metallographic image of the ingot structure in Embodiment 3; (d) is the metallographic image of the ingot structure in Embodiment 4;
[0050] Figure 4 are metallographic images of the ingot structure in the comparative examples; (a) is the metallographic image of the ingot structure in comparative example 1; (b) is the metallographic image of the ingot structure in comparative example 2;
[0051] Figure 5 It is a comparison chart of the high temperature tensile section shrinkage of Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0052] In order to better understand the above technical solution of the present invention, the technical solution of the present invention is further described below in conjunction with embodiments.
[0053] The invention discloses a high heat-plastic 980MPa grade ultra-high strength automobile steel, which comprises the following components by weight percentage: C: 0.1-0.3%, Si: 0.2-0.7%, Mn: 1-3%, Ti: 0.04-0.07%, Al: 0.02-0.07%, Ca: 0.001-0.005%, Ce: 0.0010-0.0050%, Cr: 0.2-0.4%, P≤0.013%, S≤0.002%, and the remainder Fe and inevitable impurities.
[0054] In the high heat-molding 980MPa grade ultra-high strength automobile steel of the present invention, the design principles of each component are as follows:
[0055] C is an important element in ultra-high strength steel. Increasing the C content in steel can improve the strength of the material and reduce production costs, and increase the strength level of ultra-high strength automobile steel. In the present invention, the C content is not less than 0.1%; at the same time, the increase in the C content in steel will reduce plasticity and ductility, so the C content is not higher than 0.3%. Therefore, in order to achieve the expected effect, the C content in the present invention is 0.1-0.3%.
[0056] Si element is an important deoxidizer in the smelting process and can also improve the strength of steel. Si content needs to be added to the composition. However, if the Si content is too high, string-like Al-Si inclusions will appear in the steel, causing stamping cracking. The Si content of the present invention is in the range of 0.2% to 0.7%.
[0057] Mn is an important deoxidizer in the steelmaking process. It can improve hardenability and toughness. It can also react with S in steel to generate MnS, eliminating the harmful effects of S in steel. Mn plays an important role in maintaining a certain strength and toughness of ultra-high-strength automotive steel, so the Mn content range is 1-3%.
[0058] Ti can combine with nitrogen and oxygen to form Ti-containing oxides and nitrides. In this process, Ti plays a part in deoxidation, so the Ti content is not less than 0.04%. However, too high Ti will promote the formation of large-sized TiN and cause stamping defects, so the upper limit of the Ti content is 0.07%.
[0059] S will generate MnS with Mn in steel. In rare earth treated steel, after rare earth is added to steel, due to its strong metallic property, its affinity with sulfur is much greater than its affinity with iron and sulfur. Therefore, the sulfur element in the molten steel quickly forms rare earth sulfide with the rare earth element. Since the density of rare earth sulfide is less than that of the molten steel, the rare earth sulfide floats to the protective slag under the action of buoyancy, affecting the melting of the protective slag. At the same time, the formation of rare earth sulfide affects the modification of rare earth on alumina. Therefore, S in steel should be reduced as much as possible. In the present invention, the reaction between rare earth and S should be reduced to avoid the formation of rare earth sulfide. However, too low S content requirements will have a great impact on the cost of steelmaking, which will greatly increase the cost of steelmaking. Therefore, the upper limit of S content is 0.002%.
[0060] P has a strong solid solution strengthening effect and can significantly improve the strength and hardness of steel. Therefore, the upper limit of the P content is 0.013%.
[0061] Al is a commonly used grain refining element and a commonly used deoxidizer. In order to improve the purity of molten steel and reduce the total oxygen in the steel, the lower limit of Al is 0.02%. Too high Al content will increase the cost and increase the acid-soluble aluminum content in the steel, increasing the risk of secondary oxidation. Therefore, the upper limit of Al is 0.07%.
[0062] Ca is an element that modifies inclusions. It can react with Al2O3 inclusions in steel to generate low-melting-point calcium aluminate inclusions, reduce nozzle nodules, and improve casting stability.
[0063] Cr can increase the hardenability of steel and has a secondary hardening effect. In the quenching and tempering process, it can improve the hardenability and make the steel have better comprehensive mechanical properties after quenching and tempering. The lower limit of Cr is 0.2%. The increase of Cr content will increase the tendency of high temperature temper brittleness, so the upper limit of Cr is 0.4%. Therefore, in order to achieve the expected effect, the Cr content in the present invention is 0.2-0.4%.
[0064] Ce is a rare earth element and is an important element used in the present invention to refine inclusions in steel. Ce is fed into the steel through the crystallizer wire feeding to refine inclusions. However, too high a Ce content will generate large-sized rare earth oxide inclusions, so the Ce content in the present invention is 0.0010-0.0050%.
[0065] In the composition design of the present invention, the three elements of Al, Ti and Ce should be controlled within a range at the same time, because these three elements are the key to the formation of inclusions. Different composition combinations and deoxidation sequences will have a greater impact on the types of oxides in the steel. If the Al content is too high, large-sized Al2O3 inclusions will be formed, affecting the quality of the ingot. If the Ti content is too high, the formation of TiN will be promoted. At the same time, the Ti content cannot be too low. Too low Ti content cannot reduce the oxygen in the steel to a suitable level. If the oxygen in the steel is too high, the aluminum oxide content in the steel will increase after adding Al. If the Ce content is too high, large-sized rare earth oxide inclusions will be generated in the steel. The floating time of such inclusions in the crystallizer is relatively short, which will cause the purity of the steel to decrease.
[0066] Under the premise of controlling the composition, the composition of the steel must also meet the following requirements: Al / Ce = 11-40, Ce / S = 0.5-3, where Al, Ce, and S are the weight percentages of the corresponding elements. Among them, controlling Al / Ce = 11-40: The purpose is to avoid the formation of a large number of large-sized Al-Ce composite oxides and single large-sized rare earth oxides in the steel. These oxides are difficult to remove in the molten steel, and are large in size, which can easily cause steel defects. At the same time, within this ratio range, the modification reaction of rare earth on calcium-aluminum composite inclusions can be carried out. Controlling Ce / S = 0.5-3: Because rare earth has a strong metallic property, its affinity with sulfur is much greater than its affinity with iron and sulfur. Therefore, when the sulfur element in the molten steel is high, the S element will quickly form sulfide rare earth with the rare earth element, making it difficult for the free rare earth element in the steel to modify the calcium-aluminum composite inclusions, and it is impossible to form effective Al-Ce composite inclusions, refine the grains, and strengthen the thermoplasticity of the ingot.
[0067] Among the inevitable impurities, O ≤ 0.0020%, by weight percentage.
[0068] The inclusion type of high heat-molded 980MPa grade ultra-high strength automobile steel is Al-Ca-Ce composite inclusion; the density of inclusions larger than 5 microns is ≤0.05 / mm 2 , the density of inclusions larger than 1 micron is ≤25 / mm 2 , the average diameter of inclusions is ≤2 microns. In the ingot structure, the proportion of needle-shaped bainite structure is greater than 30%, so the high-heat plasticity 980MPa grade ultra-high strength automobile steel has excellent hot plasticity.
[0069] The cross-sectional shrinkage of high heat-molding 980MPa grade ultra-high strength automotive steel is ≥40%.
[0070] The above-mentioned method for manufacturing the high heat-molding 980MPa grade ultra-high strength automobile steel comprises the following steps:
[0071] S1, smelting, using KR desulfurized hot metal and low-sulfur scrap steel as raw materials, adopting top and bottom combined blowing process in the converter, and controlling the oxygen content of the tapped steel below 600ppm by pre-deoxidation during the converter tapping process;
[0072] Specifically, according to the composition of high-heat-molded 980MPa grade ultra-high-strength automotive steel, smelting is carried out, with KR desulfurized molten iron and low-sulfur scrap steel as raw materials, and the molten iron ratio of the raw materials is controlled to be ≥88%; in order to ensure the bottom blowing effect of the converter, a top and bottom combined blowing process is adopted; in the converter tapping process, the tapping oxygen is controlled below 600ppm, and in a preferred embodiment, the tapping oxygen is controlled at 500-600ppm; the tapping temperature is controlled at 1670-1680℃, and the tapping is rapid. During the tapping process, ferrosilicon is added for pre-deoxidation, wherein the amount of ferrosilicon added is determined according to the tapping oxygen, and the specific amount added is 50-200kg / heat; lime is added for slagging during the tapping process, and the amount of lime added is 900-1100kg / heat.
[0073] S2, LF refining, adding aluminum slag during the LF heating process, adding alloys to adjust the composition of the molten steel after reaching the target temperature, and blowing argon gas at the bottom for stirring;
[0074] Specifically, the LF is heated, and 100-200 kg / furnace of aluminum slag is added to deoxidize the slag surface. The sulfur in the molten steel is kept in a relatively low range through slag making and desulfurization. After the LF is heated to the target temperature (for example, 1620-1630°C), alloys are added to the molten steel to adjust the alloy components such as Al, Cr, Si, and Mn to the target values. After the alloy is added, argon is blown bottom for stirring to ensure uniform composition of the molten steel. The argon flow rate is 160-180 L / min, and the stirring time is 4-6 min.
[0075] S3, RH refining, vacuum composition adjustment is carried out in the RH furnace, titanium alloy is added first for deoxidation, aluminum alloy is added for deoxidation after an interval of 3 to 5 minutes, and other alloys are added to adjust the steel liquid composition to the target value, and calcium wire is fed into the RH furnace for calcium treatment after breaking the vacuum;
[0076] Specifically, the vacuum composition is adjusted in the RH furnace, and the alloying process is carried out after the vacuum degree is controlled to be less than 100Pa. Titanium alloy is first added for deoxidation to reduce the oxygen content in the steel, and then aluminum alloy is added for deoxidation after an interval of 3 to 5 minutes, and other alloys are added to adjust the composition of the molten steel to the target value. During the vacuum composition adjustment process, the pure degassing time is ≥10min; after breaking the air, calcium wire is fed for calcium treatment, wherein the wire feeding speed is 160 to 180m / min. During the vacuum composition adjustment process, the amount of titanium alloy added is 120 to 140kg / heat, and the amount of aluminum alloy added is 800 to 900kg / heat.
[0077] In the above-mentioned smelting, LF refining and RH refining processes, under the premise of controlling the composition of steel, the deoxidation process is optimized, the deoxidation process (Si→Ti→Al), that is, adding ferrosilicon for pre-deoxidation during the converter steel-making process, and adding titanium alloy and aluminum alloy during RH refining. When the converter steel is tapped, ferrosilicon is added for pre-deoxidation according to different free oxygen in the steel-making process to ensure that the oxygen before refining and adding Ti is at a suitable level, while reducing the deoxidation cost; the converter steel is tapped using silicon-based deoxidation alloys for pre-deoxidation to reduce the Al2O3 generated by the subsequent addition of Al deoxidation alloys, and at the same time optimize the oxygen position before RH refining treatment to reduce the generation of large-sized clustered Al2O3. From the perspective of inclusion control, the use of Si deoxidation first can effectively reduce free oxygen. From a thermodynamic perspective, Al is a stronger deoxidizer than Si. After the subsequent addition of Al, the SiO2 product of Si deoxidation remaining in the steel can be reduced, reducing the generation of SiO2 inclusions in the steel and ensuring the purity of the molten steel.
[0078] Add ferrosilicon to the converter steel and add aluminum slag to LF refining for deoxidation to reduce the deoxidation cost; in the RH refining process, Ti is first added for deoxidation to reduce the oxygen content in the steel, and then Al is added for deoxidation and alloying. After the Ti-first deoxidation process is adopted, a certain amount of submicron TiN inclusions will be generated in the molten steel. These inclusions will play a role in refining the grains during the solidification of the ingot, thereby improving the toughness of the corners of the ingot and reducing the occurrence of ingot cracks.
[0079] S4, continuous casting wire feeding, control O≤0.002%, S≤0.002% in the tundish steel liquid, and feed rare earth wire into the continuous casting crystallizer.
[0080] Specifically, during the continuous casting process, the O content of the tundish is controlled to be ≤0.0020% and the S content is ≤0.001%, because rare earth added to steel will react with oxygen in the steel. If the oxygen content in the steel is too high, large-sized rare earth oxides will be generated, and if the sulfur content is too high, a large amount of rare earth sulfides will be generated. Both types of inclusions are undesirable, so the oxygen content and sulfur content of the molten steel before feeding the rare earth wire into the crystallizer must be controlled. Rare earth wire is fed into the continuous casting crystallizer, of which there are two types: the first is a La-Ce alloy with a rare earth content of more than 99%, wherein the La content is 25-35wt% and the Ce content is 65-85wt%; the second is a Ce rare earth wire with an external iron shell having a Ce content of 55-65%.
[0081] The specific wire feeding process is as follows: the wire feeding position is the geometric center of one side of the nozzle, that is, the intersection of 1 / 2 of the nozzle distance to the narrow side and 1 / 2 of the narrow surface, and single-wire wire feeding is adopted. Among them, the wire feeding speed is 4-8m / min, and the diameter of the rare earth wire can be 2.5mm.
[0082] When the first rare earth wire, i.e. La-Ce alloy with a rare earth content of more than 99%, is used, the steel throughput is ≥3t / min, single-wire wire feeding, the wire feeding speed is 4-5m / min, the recovery rate is 40-60%, and the rare earth content in the steel is 25-49ppm.
[0083] When the second type of rare earth wire is used, that is, rare earth wire with an external iron shell containing 55-65% Ce, the steel throughput is ≥3t / min, single-wire wire feeding, wire feeding speed is 6-8m / min, the recovery rate is 80-90%, and the rare earth content in the steel is 25-49ppm.
[0084] During the above-mentioned continuous casting wire feeding process, adjustments can be made according to the different cross-sections of the slab so that the rare earth content of the steel grade reaches the target value. During the wire feeding process of the crystallizer, no agglomeration of the protective slag was found, and no sticky slag and cracks were found in the slab. The protective slag of the furnaces fed with rare earth and those not fed with rare earth was analyzed, and no significant difference in composition was found. In this process, attention should be paid to the wire feeding speed and steel flow rate of the rare earth. During the casting process, attention should be paid to the changes in the protective slag and the thickness of the molten layer. During the continuous casting wire feeding process, increasing the steel flow rate and raising the temperature of the molten steel are beneficial to the melting rate of the rare earth wire in the molten steel, and are also beneficial to the melting of the protective slag. Therefore, it is preferred to choose a larger steel flow rate as much as possible.
[0085] The inclusion type of the high heat-molded 980MPa grade ultra-high strength automobile steel prepared above is Al-Ca-Ce composite inclusion; the density of inclusions larger than 5 microns is ≤0.05 / mm 2 , the density of inclusions larger than 1 micron is ≤25 / mm 2, the average diameter of inclusions is ≤2 microns. In the ingot structure, the proportion of needle-shaped bainite structure is greater than 30%, so the high-heat plasticity 980MPa grade ultra-high strength automobile steel has excellent hot plasticity.
[0086] The present invention designs alloy composition and optimizes preparation process, modifies and refines inclusions, and finally prepares high heat plasticity 980MPa grade ultra-high strength automobile steel with a cross-sectional shrinkage rate of ≥40% at high temperature, which effectively improves its high temperature plasticity and reduces the risk of casting defects in ultra-high strength automobile steel.
[0087] The high heat-shaped 980MPa grade ultra-high strength automobile steel and the manufacturing method of the present invention are further introduced below with reference to specific examples.
[0088] Example
[0089] In Examples 1 to 4, the method for manufacturing the high heat-molding 980 MPa grade ultra-high strength automobile steel of the present invention is adopted, and the specific process is as follows:
[0090] (1) Smelting: KR desulfurized iron and scrap steel are used as raw materials, and the water-dispersion ratio is controlled to be above 88%. To ensure the bottom blowing effect of the converter, a top-bottom combined blowing process is adopted, the oxygen level of the steel is controlled below 600ppm, the steel tapping temperature is controlled at 1670-1680°C, and the steel is tapped quickly. During the steel tapping process, ferrosilicon is added for pre-deoxidation, and the amount of ferrosilicon added is determined according to the oxygen level of the steel tapping; lime is added during the converter tapping process;
[0091] (2) LF furnace refining: The LF is heated and 100-200 kg / furnace of aluminum slag is added for deoxidation; after the LF temperature reaches the target temperature (e.g., 1620-1630°C), alloy is added to the molten steel to adjust the alloy components such as Al, Cr, Si, and Mn to reach the target values; after the alloy is added, argon is blown from the bottom for stirring to ensure that the composition of the molten steel is uniform; the argon flow rate is 160-180 L / min, and the stirring time is 4-6 min.
[0092] (3) RH refining: vacuum composition adjustment is carried out in the RH furnace, and the alloying process is carried out after the vacuum degree is controlled to be less than 100Pa. Sponge titanium is first added for deoxidation. Sponge titanium plays a part in deoxidation and produces submicron TiN at the same time. After an interval of 3 to 5 minutes, aluminum alloy is added for deoxidation, and other alloys are added to adjust the composition of the molten steel to the target value. During the vacuum composition adjustment process, the pure degassing time is guaranteed to be more than 10 minutes; after breaking the air, calcium wire is fed for calcium treatment, and the wire feeding speed is 160m / min.
[0093] (4) Continuous casting wire feeding: During the continuous casting process, the O content of the tundish is controlled to be ≤0.0020% and the S content is ≤0.002%, and rare earth wire is fed into the continuous casting crystallizer;
[0094] Wherein, the first rare earth wire is used in Examples 1 and 2, which is a La-Ce alloy with a rare earth content of more than 99%, wherein the La content is 25-35wt%, the Ce content is 65-85wt%, the steel throughput is maintained at ≥3t / min, single wire feeding, 40-60% yield, single wire feeding, wire feeding speed is 4-5m / min, and the rare earth content in the steel is 49ppm. Examples 3 and 4 use the second rare earth wire, i.e., a rare earth wire with an outer iron shell Ce content of 55-65%, the steel throughput is maintained at ≥3t / min, single wire feeding, 80-90% yield, single wire feeding, wire feeding speed is 6-8m / min, and the rare earth content in the steel is 49ppm.
[0095] Comparative Example
[0096] Comparative Examples 1 and 2 use the same process as Example 1, except that the chemical composition is different and no rare earth wire feeding treatment is performed in the crystallizer during the continuous casting process.
[0097] Table 1 shows the chemical composition of the steels of Examples 1-4 and Comparative Examples 1-2, and Table 2 shows the process parameters during the manufacturing process of Examples 1-4.
[0098] Table 1 Chemical composition of examples and comparative examples (wt%)
[0099]
[0100] Table 2 Process parameters of the manufacturing process of the embodiment
[0101]
[0102] Combination Figure 1 , Figure 2 It can be seen from the morphologies of the inclusions in the embodiments and comparative examples that the typical inclusions in the embodiments of the present invention are Al-Ca-Ce composite inclusions, which play a role in promoting nucleation and refining grains during the solidification of the ingot.
[0103] Combination Figure 3 , Figure 4 From the metallographic diagrams of the ingot structures of the embodiment and the comparative example, it can be seen that the original austenite grains of the ingot structure of the embodiment of the present invention are fine, the black pearlite structure is evenly distributed, and the acicular bainite accounts for a high proportion (greater than 30%). The original austenite grains of the comparative example ingot are coarse, the banded pearlite structure is more, and the acicular bainite structure is less. This type of ingot structure of the embodiment results in an improvement in thermoplasticity.
[0104] Figure 5It is a comparison of the high-temperature tensile section shrinkage rates of the embodiment and the comparative example materials. It can be seen from the figure that the high-temperature tensile section shrinkage rate of the high-heat plastic 980MPa grade ultra-high strength automobile steel in the embodiment is significantly greater than that of the comparative example, and the high-temperature plasticity of the high-heat plastic 980MPa grade ultra-high strength automobile steel prepared in the embodiment is significantly improved.
[0105] In summary, the present invention optimizes the composition design of high thermoplastic 980MPa grade ultra-high strength automobile steel, adds rare earth elements, adds ferrosilicon for pre-deoxidation during the converter steel-making process, and forms Al-Ce composite inclusions in the molten steel by controlling the appropriate free oxygen in the steel, optimizing the order of adding deoxidizing alloys and alloys, and ensuring the calming time during the refining process, with O≤0.0020% in the steel. Rare earth wires are fed into the crystallizer to modify the inclusions, and no deterioration of the protective slag occurs during the wire feeding process, and no slag inclusion defects occur in the slab, and finally a high thermoplastic 980MPa grade ultra-high strength automobile steel is manufactured.
[0106] It should be noted that those skilled in the art should recognize that the above embodiments are only used to illustrate the present invention and are not intended to limit the present invention. As long as they are within the spirit of the present invention, any changes or modifications to the above embodiments will fall within the scope of the claims of the present invention.
Claims
1. A high heat-molding 980MPa grade ultra-high strength automobile steel, characterized in that: It includes the following components in weight percentage: C: 0.1-0.3%, Si: 0.2-0.7%, Mn: 1-3%, Ti: 0.04-0.07%, Al: 0.02-0.07%, Ca: 0.001-0.005%, Ce: 0.0010-0.0050%, Cr: 0.2-0.4%, P≤0.013%, S≤0.002%, and the remainder Fe and inevitable impurities.
2. The high heat-molding 980MPa grade ultra-high strength automobile steel according to claim 1, characterized in that: Its composition satisfies: Al / Ce=11-40, Ce / S=0.5-3, wherein Al, Ce and S are weight percentage contents of corresponding elements respectively.
3. The high heat-molding 980MPa grade ultra-high strength automobile steel according to claim 1, characterized in that: Among the unavoidable impurities, O≤0.0020%, by weight percentage.
4. The high heat-molding 980MPa grade ultra-high strength automobile steel according to claim 1, characterized in that: The inclusion type of the high heat plastic 980MPa grade ultra-high strength automobile steel is Al-Ca-Ce composite inclusion.
5. The high heat-molding 980MPa grade ultra-high strength automobile steel according to claim 4, characterized in that: In the high heat-molded 980MPa grade ultra-high strength automobile steel, the density of inclusions larger than 5 microns is ≤ 0.05 / mm 2 , the density of inclusions larger than 1 micron is ≤25 / mm 2 , the average diameter of inclusions is ≤2 microns.
6. The high heat-molding 980MPa grade ultra-high strength automobile steel according to claim 1, characterized in that: In the high heat-molding 980MPa grade ultra-high strength automobile steel, the proportion of acicular bainite structure is greater than 30%.
7. The high heat-molding 980MPa grade ultra-high strength automobile steel according to claim 1, characterized in that: The high heat plastic 980MPa grade ultra-high strength automobile steel has a cross-sectional shrinkage rate of ≥40% at high temperature.
8. A method for manufacturing a high heat-molding 980MPa grade ultra-high strength automobile steel according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1, smelting, using KR desulfurized hot metal and low-sulfur scrap steel as raw materials, adopting top and bottom combined blowing process in the converter, and controlling the oxygen content of the tapped steel below 600ppm by pre-deoxidation during the converter tapping process; S2, LF refining, adding aluminum slag during the LF heating process, adding alloys to adjust the composition of the molten steel after reaching the target temperature, and blowing argon gas at the bottom for stirring; S3, RH refining, vacuum composition adjustment is carried out in the RH furnace, titanium alloy is added first for deoxidation, aluminum alloy is added for deoxidation after an interval of 3 to 5 minutes, and other alloys are added to adjust the steel liquid composition to the target value, and calcium wire is fed into the RH furnace for calcium treatment after breaking the vacuum; S4, continuous casting wire feeding, control O≤0.002%, S≤0.002% in the tundish steel liquid, and feed rare earth wire into the continuous casting crystallizer.
9. The method for producing high heat-plastic 980MPa grade ultra-high strength automobile steel according to claim 8, characterized in that: In step S1: The molten iron ratio in the raw material is ≥88%; The tapping temperature of the converter is 1670-1680°C, and the tapping oxygen is controlled at 500-600ppm; The deoxidizer used in the pre-deoxidation process is ferrosilicon, and the amount of ferrosilicon added is 50-200 kg / heat; 900-1100 kg / heat of lime is added during the converter tapping process, and / or In step S2: The amount of aluminum slag added is 100-200 kg / furnace; The target temperature is 1620-1630°C; The argon gas flow rate is 160-180 L / min, the stirring time is 4-6 min, and / or In step S3: During the vacuum composition adjustment process, the vacuum degree is controlled to be ≤133Pa, and the pure degassing time is ≥10min; the amount of the titanium alloy added is 120-140kg / heat; the amount of the aluminum alloy added is 800-900kg / heat, and / or In step S4: During the continuous casting wire feeding process, the wire feeding position is the intersection of 1 / 2 of the distance between the water outlet and the narrow side and 1 / 2 of the narrow surface, and single wire feeding is adopted; During the continuous casting wire feeding process, the wire feeding speed is 4 to 8 m / min; The rare earth wire is made of La-Ce alloy with a rare earth content of more than 99% or a rare earth wire with an external iron shell with a Ce content of 55-65%.
10. The method for producing high heat-plastic 980MPa grade ultra-high strength automobile steel according to claim 8, wherein in the La-Ce alloy having a rare earth content of more than 99%, the content of La is 25-35wt%, and the content of Ce is 65-85wt%.
11. The method for producing high heat-plastic 980MPa grade ultra-high strength automobile steel according to claim 9, characterized in that: When the rare earth wire is La-Ce alloy with a rare earth content of more than 99%, the wire feeding speed is 4-5 m / min, and the steel throughput is ≥3 t / min; or When the rare earth wire is a rare earth wire with a Ce content of 55-65% and an externally coated iron shell, the wire feeding speed is 6-8 m / min, and the steel throughput is ≥3 t / min.
Citation Information
Patent Citations
Method for solving center segregation of casting blank
CN102310178A
A method for processing high-purity rare earth steel
CN106609313B
A method for refining inclusions in high-purity rare earth electroslag steel
CN110257590B
Continuous casting pouring basket rare earth adding technology
CN1824430A
High-strength hot dip galvanized steel plate having excellent moldability, weak material anisotropy and ultimate tensile strength of 980 mpa or more, high-strength alloyed hot dip galvanized steel plate and manufacturing method therefor
CN103987868A